2001
DOI: 10.1136/hrt.85.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Full recovery of contraction late after acute myocardial infarction: determinants and early predictors

Abstract: OBJECTIVESTo assess the relative value of electrocardiographic, echocardiographic, angiographic, and in-hospital therapeutic indices for predicting late functional recovery after acute myocardial infarction, and to determine the variables associated with absence of recovery, partial recovery, and full recovery.DESIGNProspective observational follow up study.SETTINGTeaching hospital.PATIENTS74 consecutive patients with a first uncomplicated acute myocardial infarct.INTERVENTIONSDobutamine–atropine stress echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, other authors presented results, which emphasized the prognostic importance of revascularisation of hibernating myocardium, verified almost a direct impact of detected viability and contractile reserve on late functional recovery 20,21,24,25 .…”
Section: Number Of Recoveredmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, other authors presented results, which emphasized the prognostic importance of revascularisation of hibernating myocardium, verified almost a direct impact of detected viability and contractile reserve on late functional recovery 20,21,24,25 .…”
Section: Number Of Recoveredmentioning
confidence: 68%
“…Lancellotti et al 21 in a group of patients reperfused with thrombolytic therapy found that contractile reserve was independent predictor of full recovery of contractile function late after acute myocardial infarction. Similar results were confirmed in a pooled analysis of the currently available dates from Schinkel et al 22 .…”
Section: Number Of Recoveredmentioning
confidence: 99%